HUBUNGAN PERSEPSI SISWA KELAS X MIPA DI SMA NEGERI SEKOTA BENGKULU TAHUN AJARAN 2016/2017 TENTANG VARIASI GAYA MENGAJAR GURU DENGAN HASIL BELAJAR KIMIA - Indah Ayu Lestari; Hermansyah Amir; Salastri Rohiat (University of Bengkulu, 2017)
[RELATIONS OF STUDENTS PERCEPTION AND VARIATION TEACHING STYLE WITH CHEMISTRY LEARNING OUTCOMES AT CLASS X MIPA IN SMA NEGERI KOTA BENGKULU IN 2016/2017 ACADEMICS YEAR ] In teaching and learning activities at school, often faced with the problem of low student learning outcomes. Student learning outcomes is one indicator to measure success in the implementation of learning process. Student learning outcomes are influenced by several factors, both external and internal factors. One of the internal factors that can affect student learning outcomes is perception. The object of perception here is the variation of the teacher's teaching style. The purpose of this study is to obtain data about students' perceptions about the variation of teaching style of chemistry teacher and student chemistry learning outcomes in SMA Negeri Kota Bengkulu academic year 2016/2017. Polpulation in this research is all students of class X of MIPA in State Senior High School of Bengkulu which amounted to 1620 students. The technique of determining the sample that will be used by the researcher is Proportional Random Sampling technique and the sample is 324 students. Data analysis used in this research is descriptive analysis, normality test, linearity, correlation and hypothesis test. Based on the analysis, the correlation coefficient value is 0.232 > 0.11 (r count t > r table), and t count > t table (4,312 > 1,967), indicating that there is a significant positive correlation between students' perception about teacher teaching style variation and student's chemistry learning result.